Curable thermally conductive adhesive and its supply form

The curable thermally conductive adhesive addresses the challenge of balancing fast curing and long usable time by optimizing the gelation point and storage modulus, resulting in efficient heat transfer and reliable adhesion in electronic applications.

JP7662901B2Active Publication Date: 2025-04-15SEKISUI CHEMICAL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024526953
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-01-31
Publication Date
2025-04-15
Estimated Expiration
2044-01-31

AI Technical Summary

Technical Problem

Existing thermally conductive compositions used in electronic equipment applications, such as battery assemblies, face challenges in achieving a balance between fast curing and long usable time, particularly in terms of viscosity and adhesion properties.

Method used

A curable thermally conductive adhesive with a gelation point confirmed within 5 minutes to 60 minutes and a storage modulus of 9.0×10^4 Pa or higher after 60 minutes, achieved by optimizing the composition with a curable binder containing epoxy group-containing compounds and a thermally conductive filler.

Benefits of technology

The adhesive exhibits low viscosity and fast curing properties while maintaining a long usable time, ensuring efficient heat transfer and reliable adhesion in electronic applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662901000003
    Figure 0007662901000003
  • Figure 0007662901000004
    Figure 0007662901000004
  • Figure 0007662901000005
    Figure 0007662901000005
Patent Text Reader

Abstract

Provided is a curable thermoconductive adhesive composed of a curable composition containing a curable binder and a thermoconductive filler, wherein a gelation point at which the storage modulus and loss modulus are equal when measured by rheometer at a constant temperature of 25°C is confirmed 5-60 minutes, inclusive, after starting the rheometer measurement, and the storage modulus at 25°C 60 minutes after starting the rheometer measurement is 9.0×105Pa or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to curable thermally conductive adhesives and thermally conductive members for use in electronic applications such as battery assemblies. [Background technology]

[0002] Thermally conductive compositions are used, for example, by filling between a heat generating element and a heat sink to propagate heat generated by the heat generating element and dissipate it from the heat sink. Thermally conductive compositions are generally curable, and are often used in the cured form after filling. Thermally conductive compositions play an important role in many electronic device applications, such as battery assemblies such as lithium-ion battery (LiB) assemblies for electric vehicles (EVs), power electronic devices, electronic packaging, LEDs, solar cells, and electric grids.

[0003] For example, Patent Document 1 discloses a thermally conductive composition that includes an epoxy resin, a polyamide composition containing a polyamide that contains a tertiary amide in the main chain and is amine-terminated, an amino-functional compound containing 2 to 20 carbon atoms, a polyfunctional (meth)acrylate, and an inorganic filler, and that can be suitably used in electronic device applications such as battery assemblies. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2021-512990 Summary of the Invention [Problem to be solved by the invention]

[0005] As the number of EVs produced in the future continues to increase, improving the room temperature curing properties of thermally conductive compositions is one of the important issues in order to improve productivity. Assembly manufacturers place importance on temporary adhesive strength during the process, and after a certain amount of time, it is required that the parts be in a movable state within the process, i.e., in a state where they can be temporarily fixed or placed vertically. During the temporary adhesion, it is necessary to follow the steps and recesses between the parts, and it is important that the resin can be easily spread on the substrate with low load during the pot life. For example, an adhesive is required that can be placed vertically within one hour and that can easily spread the resin on the substrate with low load during the pot life. Furthermore, assembly manufacturers are considering shortening assembly times and, for example, while they can temporarily fasten components after one hour, they envision transporting the bonded components after 18 hours. Therefore, achieving both adhesive strength in a short period of time, such as after one day, and usable life is an important issue when considering efficiency and workability.

[0006] In Patent Document 1, acrylate is added to increase the fast curing property, and polyamide is used in consideration of health hazard concerns. Polyamide has a low molecular weight, but the viscosity increases due to the interaction. Therefore, even if fast curing is possible, a long pot life cannot be achieved.

[0007] Therefore, an object of the present invention is to provide a curable thermally conductive adhesive that has low viscosity, rapid curing properties, and a long pot life. [Means for solving the problem]

[0008] As a result of extensive investigations, the inventors have found that the above-mentioned problems can be solved by adjusting the storage modulus at 25°C to be a certain level or higher 60 minutes after the start of the rheometer measurement, and by checking the gel point at 5 to 60 minutes after the start of the rheometer measurement. That is, the present invention provides the following [1] to

[13] .

[0009] [1] A curable thermally conductive adhesive comprising a curable composition including a curable binder and a thermally conductive filler, wherein, when rheometer measurement is performed at a constant temperature of 25°C, a gel point at which the storage modulus and loss modulus are equal is confirmed 5 to 60 minutes after the start of the rheometer measurement, and the storage modulus at 25°C 60 minutes after the start of the rheometer measurement is 9.0 × 10 5 A curable thermally conductive adhesive having a viscosity of 100 Pa or more. [2] When measured with the rheometer, the loss modulus of the curable thermally conductive adhesive at 25°C after 15 minutes from the start of the rheometer measurement is 3.0 x 10 5 The curable thermally conductive adhesive according to [1], wherein the thermal conductivity is 0.01 Pa or less. [3] The curable thermally conductive adhesive according to [1] or [2], wherein the binder contains an epoxy group-containing compound. [4] The curable thermally conductive adhesive according to any one of [1] to [3], wherein the binder contains at least one of an amine and a thiol. [5] The curable thermally conductive adhesive according to any one of [1] to [4], wherein the binder contains an epoxy group-containing compound and an amine. [6] The curable thermally conductive adhesive according to [3] or [5], wherein the epoxy group-containing compound comprises a monofunctional epoxy group-containing compound. [7] The curable thermally conductive adhesive according to any one of [1] to [6], wherein the binder contains a Mannich base. [8] The curable thermally conductive adhesive according to any one of [1] to [7], wherein the curable composition contains a polyfunctional acrylate compound, an epoxy group-containing compound, and an amine. [9] The curable thermally conductive adhesive according to any one of [1] to [8], wherein an equivalent ratio, which is the ratio of the equivalent of active hydrogen in the curing agent to the equivalent of functional groups in a component constituting the main agent contained in the curable composition, is 1.05 or more and 2.9 or less.

[10] A supply form of the curable thermally conductive adhesive described in claim 1 or 2, in which a first agent containing a main agent of the binder and a second agent containing a curing agent that hardens when mixed with the first agent are filled in separate containers.

[11] A supply form of the curable thermally conductive adhesive described in

[10] , wherein the difference between the viscosity of the first part and the compressive load of the second part is 450 N or less.

[12] A supply form of the curable thermally conductive adhesive described in

[10] or

[11] , in which the ratio of the functional group concentration of the second agent to the functional group concentration of the first agent is 1.05 or more and 2.9 or less.

[13] Use of the curable thermally conductive adhesive according to any one of the above items [1] to

[10] as at least one of the gap materials between battery cells, between a battery cell and a module housing, between a battery module and a battery pack housing, and between a battery cell and a battery pack housing. Effect of the Invention

[0010] According to the present invention, it is possible to provide a curable thermally conductive adhesive that has low viscosity, rapid curing properties, and a long pot life. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a schematic diagram showing a container set according to one embodiment. [Diagram 2] FIG. 11 is a schematic diagram showing a container set according to another embodiment. [Diagram 3] 1 is a perspective view showing a representative configuration of a battery module according to the present invention; [Figure 4] 1 is a perspective view showing a typical configuration of a battery cell included in a battery module. [Diagram 5] FIG. 1 is a perspective view showing a battery assembly having a cell-to-pack structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] [Curing heat conductive adhesive] The curable thermally conductive adhesive of the present invention will now be described in detail. The curable thermally conductive adhesive of the present invention comprises a curable composition containing a curable binder and a thermally conductive filler. In the present invention, when the storage modulus and loss modulus at 25°C are measured with a rheometer (hereinafter, the measurement is also referred to as "rheometer measurement"), a gel point (hereinafter, simply referred to as "gel point") at which the storage modulus and loss modulus become equal is confirmed 5 to 60 minutes after the start of the measurement. Furthermore, when the storage modulus at 25°C is 9.0 x 10 5 Pa or more.

[0013] <Gel point> If the gel point is confirmed within 5 minutes from the start of the rheometer measurement, the pot life will be short, and the adhesive will become highly viscous immediately after application to the substrate, making it difficult to spread the adhesive over the substrate. If the gel point is confirmed beyond 60 minutes from the start of the rheometer measurement, the development of excellent adhesive strength will be delayed, making it difficult for the adhesive to have fast curing properties. From these perspectives, the gel point is preferably confirmed 5 to 50 minutes, more preferably 10 to 40 minutes, from the start of the rheometer measurement. Here, the gel point refers to the point at which the storage modulus and loss modulus of the adhesive become equal when measured by a rheometer at 25° C. As the rheometer, for example, the rheometer “MCR-302e” manufactured by Anton Paar Corporation may be used. The method for measuring the time at which the gel point is confirmed (hereinafter also referred to as "gelation time") is as described in the Examples. The gel point can be adjusted to within the above-mentioned range by, for example, appropriately adjusting the type and amount of the main agent of the binder component and the curing agent.

[0014] <Storage modulus> The storage modulus at 25°C after 60 minutes from the start of the rheometer measurement (hereinafter also referred to as "elastic modulus G'(60)") was 9.0 x 10 5If the elastic modulus is less than 9.2×10 Pa, it becomes difficult for the adhesive to exhibit excellent adhesiveness. 5 Pa or more, and 1.0×10 6 The upper limit of the elastic modulus G'(60) is not particularly limited, but is preferably 1.0×10 Pa or more from the viewpoint of enabling the adhesive to exhibit appropriate adhesiveness. 7 Pa or less, more preferably 8.0×10 6 Pa or less, and more preferably 5.0×10 6 Pa or less. The elastic modulus G'(60) can be obtained by the measurement method described in the Examples.

[0015] The adhesive of the present invention has a loss modulus at 25°C (hereinafter also referred to as "elastic modulus G''(15)") of 3.0 x 10 5 Pa or less, and 2.5×10 5 Pa or less, and more preferably 2.0×10 5 It is more preferable that the elastic modulus G''(15) is 2.0 x 10 Pa or less. By having the elastic modulus G''(15) be equal to or less than the above upper limit, the adhesive will not harden too quickly, making it easier to extend the usable time. Also, for example, the adhesive strength after 18 hours is more likely to be at least a certain level. On the other hand, from the viewpoint of ensuring a certain degree of rapid hardening of the adhesive, the elastic modulus G''(15) is 2.0 x 10 3 Pa or more, and 2.2×10 3 More preferably, the pressure is 2.5×10 Pa or more. 3 It is more preferable that the pressure is 1 Pa or more. The elastic modulus G''(15) can be obtained by the measurement method described in the Examples.

[0016] The adhesive of the present invention has a storage modulus at 25° C. 15 minutes after the start of rheometer measurement (hereinafter, simply referred to as “elastic modulus G′(15)”) of 2.5×10 6 Pa or less, and 2.0×10 6 Pa or less is more preferable, and 1.7×10 6It is more preferable that the elastic modulus G'(15) is 5.0×10 Pa or less. By having the elastic modulus G'(15) be equal to or less than the upper limit, the adhesive will not harden too quickly, making it easier to extend the usable time. In addition, the adhesive strength after, for example, 18 hours is more likely to be at least a certain level. On the other hand, from the viewpoint of ensuring a certain degree of rapid hardening of the adhesive, the elastic modulus G'(15) is 5.0×10 2 Pa or more, and 8.0×10 2 Pa or more is more preferable, and 1.0×10 3 It is more preferable that the pressure is 1 Pa or more. The elastic modulus G'(15) can be obtained by the measurement method described in the Examples. The elastic modulus G'(60), the elastic modulus G''(15), and the elastic modulus G'(15) can be adjusted to within the above-mentioned ranges by, for example, appropriately adjusting the type and amount of the main agent of the binder component and the curing agent. The elastic modulus G'(60) and the elastic modulus G'(15) can also be easily increased by accelerating the curing rate.

[0017] <Thermal conductivity> The adhesive of the present invention preferably has a thermal conductivity of 1.3 W / (m·K) or more, more preferably 1.5 W / (m·K) or more, and even more preferably 1.6 W / (m·K) or more of its cured product. The adhesive has good thermal conductivity when the thermal conductivity of the cured product is equal to or greater than these lower limits. Therefore, for example, when used in a battery cell assembly, the heat generated from the battery cell can be efficiently transferred to the module housing or the battery pack via the cured product of the adhesive (thermally conductive member), and an excessive increase in the temperature of the battery cell can be suppressed. The higher the thermal conductivity, the better, but in practice, it is, for example, 7.0 W / (m·K) or less. The thermal conductivity can be measured by a method in accordance with ASTM D5470-06. Specifically, a larger amount of adhesive is placed on the measurement die (which is the heat generating element) to cover it, then it is sandwiched between heat sinks and compressed with a load of 30 psi until the adhesive thickness is 1.0 mm, 1.5 mm, and 2.0 mm, and the thermal resistance is measured for each thickness. The thickness can be adjusted with a spacer. For these three thermal resistance values, a graph is created with thickness on the horizontal axis and thermal resistance on the vertical axis, and an approximation line between the three points is found using the least squares method. The slope of this approximation line is then taken as the thermal conductivity.

[0018] <Adhesive strength> The adhesive of the present invention preferably has an adhesive strength (hereinafter also referred to as "adhesive strength 1") of 0.03 MPa or more and 0.7 MPa or less, more preferably 0.05 MPa or more and 0.5 MPa or less, and even more preferably 0.08 MPa or more and 0.3 MPa or less, one hour after the start of mixing the components. When adhesive strength 1 is equal to or more than the above lower limit, the minimum adhesive strength required for temporarily fixing the members can be ensured. When adhesive strength 1 is equal to or less than the above upper limit, the members can be easily peeled off after being temporarily fixed when, for example, correcting the position of the members.

[0019] In addition, the adhesive of the present invention preferably has an adhesive strength (hereinafter also referred to as "adhesive strength 2") of 0.8 MPa or more, more preferably 0.9 MPa or more, and even more preferably 1.2 MPa or more, 18 hours after the start of mixing the components. When adhesive strength 2 is equal to or greater than the lower limit, the adhesive is sufficiently cured, and for example, when members bonded via the adhesive are transported, the members can be prevented from peeling off even if they are subjected to vibrations during transportation. The upper limit of adhesive strength 2 is not particularly limited, but is practically, for example, 5 MPa or less, preferably 3 MPa or less, and more preferably 2 MPa or less. The above-mentioned adhesive strengths can all be obtained by the measurement methods described in the Examples.

[0020] [binder] The adhesive of the present invention includes a curable binder. The curable binder may be heat-curable, light-curable, or moisture-curable, but is preferably heat-curable. The binder may be either a one-component curable type or a two-component curable type, but is preferably a two-component curable type. The two-component curing type is used by mixing the first component containing the base agent and the second component containing the hardener, and hardening is initiated by mixing the first and second components. Therefore, in the two-component curing type, it is preferable to use a hardener that hardens when mixed with the first component, the base agent. In addition, it is preferable to use a hardener that can be mixed with the first component, the base agent, and hardened at room temperature (25°C).

[0021] The binder is preferably any one of a urethane-based, silicone-based, acrylic-based, epoxy-based, and an organic polymer having a hydrolyzable silyl group, and among these, an epoxy-based is preferred. The use of these specific binders makes it easier to impart rapid curing properties to the adhesive and to extend its usable life. The binder may be used alone or in combination of two or more kinds.

[0022] Here, the urethane-based binder may be, for example, one that is made of a polyol compound as a base agent and a polyisocyanate compound as a curing agent. The silicone-based binder may be either a condensation curing type silicone resin or an addition reaction curing type silicone resin, but is preferably an addition reaction curing type silicone resin.The addition reaction curing type silicone resin is preferably composed of a silicone resin constituting a main component and a curing agent that cures the main component.For example, in the case of the addition reaction curing type silicone resin, it is preferable to use an organopolysiloxane having an alkenyl group as the main component and an organohydrogenpolysiloxane as the curing agent.

[0023] The epoxy binder preferably comprises an epoxy group-containing compound as a base agent and a curing agent. The acrylic binder may be any component that forms an acrylic polymer by curing, and examples thereof include alkyl (meth)acrylate, hydroxyalkyl (meth)acrylate, (meth)acrylic acid, (meth)acrylamides, and urethane (meth)acrylate. The acrylic binder may also contain a vinyl monomer that is copolymerizable with the acrylic compound. Furthermore, the acrylic binder may be at least partially a polymer of an acrylic compound, or a copolymer of an acrylic compound and a vinyl monomer. The acrylic binder may also be a monofunctional acrylate compound or a polyfunctional acrylate compound.

[0024] The organic polymer having a hydrolyzable silyl group has a hydrolyzable silyl group, and after hydrolysis by moisture such as humidity to form a silanol group, the silanol groups can be polycondensed with each other or with the hydrolyzable silyl group to form a siloxane bond. As a result, the organic polymer forms a crosslinked structure and hardens to obtain a rubber-like elastic body. The silanol group means a hydroxyl group (Si-OH) directly bonded to a silicon atom. The hydrolyzable silyl group is preferably an alkoxysilyl group, and specific examples thereof include a trimethoxysilyl group, a dimethoxysilyl group, a triethoxysilyl group, and a diethoxysilyl group. On the other hand, the organic polymer can be polyether such as polyalkylene oxide. The case where an epoxy-based binder is used will be described in detail below.

[0025] (Epoxy group-containing compound) As described above, when the binder is an epoxy-based binder, it is preferable that the binder contains an epoxy group-containing compound. By using the epoxy group-containing compound, the adhesive strength of the adhesive can be easily adjusted to an appropriate range. The epoxy group-containing compound may be a compound having one or more epoxy groups. The epoxy group-containing compound may be a polyfunctional epoxy group-containing compound having two or more epoxy groups, or a monofunctional epoxy group-containing compound having one epoxy group.

[0026] The adhesive of the present invention preferably contains at least a polyfunctional epoxy group-containing compound. By containing the polyfunctional epoxy group-containing compound, the adhesive can increase the reaction rate between the base agent and the curing agent, shorten the time until the gel point is confirmed, and easily exhibit fast curing properties. The adhesive may further contain a monofunctional epoxy group-containing compound in addition to the polyfunctional epoxy group-containing compound. By further containing the monofunctional epoxy group-containing compound, the adhesive can have an appropriate reaction speed between the base agent and the curing agent, making it easier to extend the pot life and lower the initial viscosity. Furthermore, it can prevent the time at which the gel point is confirmed from becoming too early.

[0027] When a polyfunctional epoxy resin and a monofunctional epoxy resin are used in combination, the mass ratio of the monofunctional epoxy resin to the polyfunctional epoxy resin (monofunctional / polyfunctional) is preferably 10 / 90 or more and 90 / 10 or less, more preferably 15 / 85 or more and 75 / 25 or less, even more preferably 20 / 80 or more and 70 / 30 or less, and still more preferably 25 / 75 or more and 60 / 40 or less.

[0028] The polyfunctional epoxy group-containing compound may be bifunctional or trifunctional, and preferably bifunctional epoxy group-containing compound is used.Specific examples of the polyfunctional epoxy group-containing compound include phenol novolac type epoxy resin, resorcinol type epoxy resin, epoxy resin having bisphenol skeleton, epoxy resin having naphthalene skeleton, epoxy resin having fluorene skeleton, epoxy resin having biphenyl skeleton, epoxy resin having bi(glycidyloxyphenyl)methane skeleton, epoxy resin having xanthene skeleton, epoxy resin having anthracene skeleton, epoxy resin having pyrene skeleton, and other epoxy resin having aromatic skeleton. Further examples include epoxy resins having an alicyclic skeleton, such as epoxy resins having a dicyclopentadiene skeleton and epoxy resins having an adamantane skeleton. Further examples include aliphatic epoxy resins such as polyalkylene glycol diglycidyl ethers, such as butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, trimethylolpropane polyglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and polytetramethylene glycol diglycidyl ether. Furthermore, hydrogenated or modified products of the above-listed epoxy resins can also be used as the epoxy resin.

[0029] Examples of the epoxy resin having a bisphenol skeleton include epoxy resins having a bisphenol skeleton of bisphenol A type, bisphenol F type, or bisphenol S type. The resorcinol type epoxy resin may, for example, be resorcinol diglycidyl ether. Examples of the epoxy resin having a naphthalene skeleton include 1,2-diglycidylnaphthalene, 1,5-diglycidylnaphthalene, 1,6-diglycidylnaphthalene, 1,7-diglycidylnaphthalene, 2,7-diglycidylnaphthalene, triglycidylnaphthalene, and 1,2,5,6-tetraglycidylnaphthalene. Examples of the epoxy resin having a fluorene skeleton include 9,9-bis(4-glycidyloxyphenyl)fluorene, 9,9-bis(4-glycidyloxy-3-methylphenyl)fluorene, 9,9-bis(4-glycidyloxy-3-chlorophenyl)fluorene, 9,9-bis(4-glycidyloxy-3-bromophenyl)fluorene, 9,9-bis(4-glycidyloxy-3-fluorophenyl)fluorene, 9,9-bis(4-glycidyloxy-3-methoxyphenyl)fluorene, 9,9-bis(4-glycidyloxy-3,5-dimethylphenyl)fluorene, 9,9-bis(4-glycidyloxy-3,5-dichlorophenyl)fluorene, and 9,9-bis(4-glycidyloxy-3,5-dibromophenyl)fluorene.

[0030] Examples of the epoxy resin having a biphenyl skeleton include 4,4'-diglycidylbiphenyl and 4,4'-diglycidyl-3,3',5,5'-tetramethylbiphenyl. Examples of the epoxy resin having a bi(glycidyloxyphenyl)methane skeleton include 1,1'-bi(2,7-glycidyloxynaphthyl)methane, 1,8'-bi(2,7-glycidyloxynaphthyl)methane, 1,1'-bi(3,7-glycidyloxynaphthyl)methane, 1,8'-bi(3,7-glycidyloxynaphthyl)methane, 1,1'-bi(3,5-glycidyloxynaphthyl)methane, 1,8'-bi(3,5-glycidyloxynaphthyl)methane, 1,2'-bi(2,7-glycidyloxynaphthyl)methane, 1,2'-bi(3,7-glycidyloxynaphthyl)methane, and 1,2'-bi(3,5-glycidyloxynaphthyl)methane.

[0031] Examples of the epoxy resin having a xanthene skeleton include 1,3,4,5,6,8-hexamethyl-2,7-bis-glycidylmethoxy-9-phenyl-9H-xanthene, etc. Examples of the epoxy resin having an anthracene skeleton include those having one or more anthracene skeletons and two or more epoxy groups or glycidyl groups in one molecule.

[0032] The epoxy resin having a pyrene skeleton includes those having one or more pyrene skeletons and two or more epoxy groups or glycidyl groups in one molecule. Examples of the epoxy resin having a dicyclopentadiene skeleton include dicyclopentadiene dioxide and phenol novolac epoxy resin having a dicyclopentadiene skeleton. Examples of the epoxy resin having an adamantane skeleton include 1,3-bis(4-glycidyloxyphenyl)adamantane and 2,2-bis(4-glycidyloxyphenyl)adamantane.

[0033] Among the above bifunctional epoxy group-containing compounds, from the viewpoint of increasing the storage modulus and easily improving the adhesive strength and mechanical strength, epoxy resins having an aromatic skeleton are preferred, and among them, bisphenol-type epoxy resins, which are epoxy resins having a bisphenol skeleton, are preferred. It is also preferred to use an epoxy resin having an aromatic skeleton in combination with an aliphatic epoxy resin. The bifunctional epoxy group-containing compound may be used alone or in combination of two or more kinds.

[0034] Examples of the monofunctional epoxy group-containing compound include phenyl glycidyl ethers such as alkylphenyl glycidyl ethers represented by phenyl glycidyl ether, 4-t-butylphenyl glycidyl ether, cresyl glycidyl ether, and nonylphenyl glycidyl ether, and monofunctional epoxy group-containing compounds having an aromatic ring such as 1-glycidylnaphthalene and 2-glycidylnaphthalene. As the monofunctional epoxy group-containing compound having an aromatic ring, an epoxy group-containing compound having a phenyl group is more preferable. By using a monofunctional epoxy group-containing compound having an aromatic ring, it is easy to increase the storage modulus and increase the adhesive strength.

[0035] In addition, as the monofunctional epoxy group-containing compound, from the viewpoint of high safety of raw materials, aliphatic monofunctional epoxy group-containing compounds are also preferred, specifically, glycidyl ethers of aliphatic alcohols, etc. can be mentioned. Here, the aliphatic alcohol may be one having a branched structure or one having a straight chain, but from the viewpoint of improving elongation, it is preferable that it is a straight chain. In addition, the aliphatic alcohol may have, for example, about 4 to 24 carbon atoms, but preferably has 10 to 20 carbon atoms. In addition, the aliphatic alcohol is preferably a saturated aliphatic alcohol from the viewpoint of improving elongation. Specific examples of the glycidyl ethers of aliphatic alcohols include butyl glycidyl ether, decyl glycidyl ether, lauryl glycidyl ether, myristyl glycidyl ether, cetyl glycidyl ether, and stearyl glycidyl ether. The monofunctional epoxy group-containing compound may be other than the above, and examples thereof include monofunctional epoxy group-containing compounds having a glycidyl group but not having an ether group, such as 1,2-epoxybutane and propylene oxide. The monofunctional epoxy group-containing compound may be used alone or in combination of two or more kinds.

[0036] The epoxy group-containing compound may have a molecular weight of, for example, 2000 or less, preferably 1000 or less, more preferably 500 or less. By using an epoxy group-containing compound having a molecular weight of a certain value or less, the viscosity of the adhesive can be reduced, and the thermally conductive filler can be highly filled. The molecular weight of the epoxy group-containing compound is, for example, 100 or more, preferably 150 or more, more preferably 200 or more, and even more preferably 250 or more. By setting the molecular weight of the epoxy group-containing compound to a certain value or more, the crosslink density can be prevented from becoming higher than necessary, and the elongation can be easily improved. The epoxy group-containing compound is preferably liquid at room temperature (25°C).

[0037] The epoxy equivalent of the epoxy group-containing compound is preferably 1000 g / eq or less, more preferably 500 g / eq or less, even more preferably 375 g / eq or less, and is preferably 100 g / eq or more, more preferably 125 g / eq or more, even more preferably 140 g / eq or more.

[0038] The epoxy group-containing compound is preferably liquid at room temperature (25°C). The viscosity of the epoxy resin at 25°C is not particularly limited, but may be, for example, 50 Pa·s or less, and preferably 10 Pa·s or less. The viscosity of the epoxy resin at 25°C is not particularly limited, but may be, for example, 0.5 mPa·s or more, or 1 mPa·s or more. The viscosity of the epoxy resin and the amine compound described later was measured using an E-type viscometer at 10 rpm and 25°C.

[0039] The content of the epoxy group-containing compound in the adhesive is, for example, 2% by mass or more and 20% by mass or less based on the total amount of the curable composition. When the content of the epoxy group-containing compound is 2% by mass or more, it is easy to increase the adhesive strength and elongation. When the content is 20% by mass or less, uncured epoxy group-containing compound components are unlikely to exist, and it is possible to prevent the adhesion from being hindered by the uncured components. The content of the epoxy group-containing compound is preferably 3 mass % or more and 15 mass % or less, more preferably 4 mass % or more and 12 mass % or less, and even more preferably 5 mass % or more and 10 mass % or less, based on the total amount of the curable composition.

[0040] (hardening agent) The binder preferably contains a curing agent that cures the base material, and more specifically, it is preferable that the binder contains at least one of amine and thiol. At least one of amine and thiol is preferably used when the binder contains an epoxy group-containing compound. By containing amine or thiol as a curing agent, the binder can be easily adjusted to a practical curing speed at room temperature. In addition, the adhesive strength of the adhesive can be easily increased.

[0041] The amine may be a polyamine such as a diamine or a triamine, or a monoamine, with polyamines such as a diamine or a triamine being preferred.

[0042] Specific examples of amines include polyoxyalkyleneamines such as polyoxyethylene diamine, poly(oxyethylene / oxypropylene) diamine, polyoxypropylene diamine, poly(oxybutylene / oxypropylene) diamine, polyethylene glycol bis(propylamine), trimethylolpropane poly(oxypropylene) triamine, glyceryl poly(oxypropylene) triamine, and methoxypoly(oxyethylene / oxypropylene)-2-propylamine; m-phenylenediamine, p-phenylenediamine, m-xylylenediamine, p-xylylenediamine, tolylene-2,4-diamine, tolylene-2,6-diamine, mesitylene-2,4-diamine, mesitylene-2,6-diamine, 3,5-diethyltolylene-2,4-diamine, 3,5-diethyltolylene-2,6-diamine, biphenylenediamine, and 4,4-diamine. Aromatic ring-containing amines such as reaction products of nodiphenylmethane, 2,5-naphthylenediamine, 2,6-naphthylenediamine, m-xylylenediamine and styrene, 1,6-hexanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, 1,14-tetradecanediamine, 1,16-hexadecanediamine, 1,18-octadecanediamine, Examples of the amines include aliphatic amines such as candiamine, 1,20-eicosanediamine, 2-methyl-1,8-octanediamine, 2-methyl-1,9-nonanediamine, and 2,7-dimethyl-1,8-octanediamine; alicyclic amines such as 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, cyclohexanediamine, methylcyclohexanediamine, and isophoronediamine; and amidoamines. Examples of amidoamines include those obtained by reacting an aliphatic dicarboxylic acid such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, or azelaic acid, or a carboxylic acid compound such as a fatty acid or a dimer acid, with an aliphatic polyamine or a polyamine having a polyoxyalkylene chain.

[0043] Also, as the amine, a Mannich base may be used. The Mannich base may be any Mannich base that can be used in an amine curing agent, and may be, for example, one obtained by the reaction of a phenolic compound, an aldehyde compound, and an amine compound. By containing a Mannich base using a phenolic compound, the phenol structure contained in the Mannich base promotes the reaction between the base material and the curing agent, and the time at which the gel point is confirmed is shortened, making it easier to exhibit excellent fast curing properties. Among the Mannich bases, it is preferable to use a phenalkamine type Mannich base.

[0044] Among the above, from the viewpoint of making the reaction rate with the base agent at a certain level or higher and easily ensuring fast curing, it is more preferable to use polyamines, especially triamines, and it is even more preferable to use diamines and triamines in combination. Diamines and triamines have different reaction rates with the base agent, and by using two or more amines with different reaction rates in combination, it is possible to partially proceed the reaction between the base agent and the curing agent, so that the time at which the gel point is confirmed is within a certain range, and the pot life can be extended while ensuring fast curing. In this case, it is more preferable that both the diamines and triamines are polyoxyalkyleneamines.

[0045] In addition, when an amidoamine is used, it is preferable to use the amidoamine in combination with a diamine or triamine other than the amidoamine. Furthermore, when a Mannich base is used, it is preferable to use the Mannich base in combination with a diamine or triamine other than the Mannich base as the amine curing agent, and it is more preferable to use the Mannich base in combination with a triamine. In these cases, it is preferable that both the diamine and the triamine are polyoxyalkyleneamines. As described above, by using two types of amines as the amine curing agent, the time at which the gel point is confirmed can be set within a predetermined range, and the pot life can be extended while ensuring fast curing properties.

[0046] From the viewpoint of increasing the fast curing property and reducing the viscosity of the adhesive before curing, the molecular weight of the amine used as the curing agent is preferably 3000 or less, more preferably 1000 or less, even more preferably 600 or less, and even more preferably 500 or less. In addition, the molecular weight of the amine curing agent is not particularly limited, but is, for example, 100 or more, preferably 150 or more, and more preferably 200 or more.

[0047] From the viewpoint of increasing the fast curing property and reducing the viscosity of the adhesive before curing, the viscosity of the amine used as the curing agent at 25°C is preferably 15 Pa·s or less, more preferably 10 Pa·s or less, even more preferably 5 Pa·s or less, and even more preferably 3 Pa·s or less. The viscosity of the amine curing agent at 25°C is not particularly limited, but is, for example, 0.03 Pa·s or more, preferably 0.05 Pa·s or more, and more preferably 0.07 Pa·s or more.

[0048] The content of the amine in the adhesive is, for example, 2% by mass or more and 20% by mass or less based on the total amount of the curable composition. When the content of the amine is 2% by mass or more, the base agent is sufficiently cured, and it becomes easier to increase the elastic modulus G'(60) and adhesive strength. When the content of the amine is 20% by mass or less, the base agent can be cured without containing an excessive amount of amine. The amine content is preferably from 3 mass % to 15 mass %, more preferably from 4 mass % to 12 mass %, and further preferably from 5 mass % to 10 mass %, based on the total amount of the curable composition.

[0049] Examples of the thiol include polythiols such as dithiols and trithiols. Specific examples of the thiol include esters of polyols and mercapto organic acids such as pentaerythritol tetrakis(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, and trimethylolpropane tris(3-mercaptobutyrate), aliphatic thiols such as alkanedithiols, and aromatic ring-containing thiols such as xylylenedithiol.

[0050] The active hydrogen equivalent of the amine and thiol contained in the adhesive is not particularly limited, but is, for example, 15 g / eq or more, preferably 25 g / eq or more, more preferably 30 g / eq or more, and is, for example, 250 g / eq or less, preferably 200 g / eq or less, more preferably 150 g / eq or less.

[0051] In the present invention, when an epoxy-based binder is used, it is preferable that the binder further contains a polyfunctional acrylate compound as a main agent in addition to an epoxy group-containing compound. That is, the binder may be composed of an epoxy group-containing compound as a main agent and a curing agent represented by an amine, or may be composed of an epoxy group-containing compound as a main agent, a polyfunctional acrylate compound, and a curing agent represented by an amine. The polyfunctional acrylate compounds used in combination with the epoxy group-containing compound are as follows.

[0052] (Polyfunctional acrylate compound) A polyfunctional acrylate compound is a compound having a number of functional groups (i.e., the number of (meth)acryloyl groups) of 2 or more. Since a polyfunctional acrylate compound reacts quickly with the above-mentioned curing agent, particularly with an amine, the use of a polyfunctional acrylate compound makes it easier to confirm the gel point early, imparts fast curing properties to the adhesive, and imparts a certain adhesive strength at the initial stage of curing. As the polyfunctional acrylate compound, it is preferable to use a polyfunctional (meth)acrylate, and it is more preferable to use an ester of a polyfunctional polyol and (meth)acrylic acid. In addition, in this specification, "(meth)acryloyl group" means either an acryloyl group or a methacryloyl group, "(meth)acrylate" means either an acrylate or a methacrylate, and the same applies to other similar terms.

[0053] Examples of bifunctional polyfunctional acrylate compounds include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, dimethyloltricyclodecane di(meth)acrylate, ethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, and triplyl glycol di(meth)acrylate. Examples of the di(meth)acrylate include pyrene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethylene oxide-added bisphenol A di(meth)acrylate, propylene oxide-added bisphenol A di(meth)acrylate, ethylene oxide-added bisphenol F di(meth)acrylate, dimethylol dicyclopentadienyl di(meth)acrylate, ethylene oxide-modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, and polybutadiene diol di(meth)acrylate.

[0054] Examples of the polyfunctional acrylate compounds having three or more functional groups include alkylene oxide-added trimethylolpropane tri(meth)acrylates such as trimethylolpropane tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethylene oxide-added trimethylolpropane tri(meth)acrylate, and propylene oxide-added trimethylolpropane tri(meth)acrylate, caprolactone-modified trimethylolpropane tri(meth)acrylate, and ethylene oxide-added isocyanuric acid tri(meth)acrylate. tetra(meth)acrylate, propylene oxide-added glycerin tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, alkylene oxide-added pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol octa(meth)acrylate, tetrapentaerythritol deca(meth)acrylate, tripentaerythritol hepta(meth)acrylate, and tetrapentaerythritol nona(meth)acrylate.

[0055] The number of functional groups of the polyfunctional acrylate compound is preferably 3 or more, more preferably 4 or more, and even more preferably 5 or more. When the number of functional groups of the polyfunctional acrylate compound is increased, the time when the gel point is confirmed is shortened, the fast curing property is improved, and the adhesive strength at the initial stage of curing is likely to be increased. The upper limit of the number of functional groups of the polyfunctional acrylate compound is not particularly limited, but may be, for example, 10 or less, or 8 or less.

[0056] The molecular weight of the polyfunctional acrylate compound is preferably a certain value or less from the viewpoint of increasing the fast curing property and reducing the viscosity of the adhesive before curing. The specific molecular weight of the polyfunctional acrylate compound may be, for example, 5000 or less, but is preferably 3000 or less, more preferably 1000 or less, and even more preferably 700 or less. In addition, the molecular weight of the polyfunctional acrylate compound is, for example, 150 or more, preferably 200 or more, more preferably 250 or more, and even more preferably 450 or more. By setting the molecular weight of the polyfunctional acrylate compound to a certain value or more, the compression load at the initial curing stage is appropriately reduced, and the crosslinking density can be prevented from becoming higher than necessary, making it easier to improve the elongation and adhesive strength. The polyfunctional acrylate compound is preferably liquid at room temperature (25° C.) in order to facilitate lowering the viscosity of the adhesive before curing.

[0057] The functional group equivalent of the polyfunctional acrylate compound is not particularly limited, but is preferably 500 g / eq or less, more preferably 300 g / eq or less, even more preferably 150 g / eq or less, and is preferably 75 g / eq or more, more preferably 80 g / eq or more, even more preferably 85 g / eq or more.

[0058] In the adhesive, the ratio of the number of functional groups of the polyfunctional acrylate compound to the number of functional groups of the epoxy resin may be about 0.1 to 1.5, but is preferably 0.2 to 1.2, more preferably 0.3 to 1.0, and even more preferably 0.4 to 0.85. When the ratio of the number of functional groups of the polyfunctional acrylate compound is within a predetermined range, the amine and the polyfunctional acrylate compound are cured preferentially in the initial stage, and fast curing properties are exhibited, while the reaction between the amine and the epoxy resin is suppressed, so that the compressive load in the initial stage of curing is kept low and the pot life can be extended.

[0059] The content of the polyfunctional acrylate compound is, for example, 10% by mass or less, preferably 8% by mass or less, based on the total amount of the curable composition. When the content of the polyfunctional acrylate compound is equal to or less than the upper limit, the polyfunctional acrylate compound prevents the initial curing from proceeding too much, and the usable time is easily extended. In addition, when the content of the polyfunctional acrylate compound is reduced, the moisture resistance is also improved. Therefore, for example, even if the composition is used for a long time under high temperature and high humidity after curing, the composition can maintain a high adhesive strength. The content of the polyfunctional acrylate compound is more preferably 6% by mass or less, and even more preferably 4% by mass or less. In order to achieve rapid curing and increase the adhesive strength in the early stage of curing, the content of the polyfunctional acrylate compound should be at least a certain amount, and is, for example, 0.3 mass% or more, preferably 0.5 mass% or more, more preferably 1 mass% or more, and even more preferably 1.5 mass% or more, based on the total amount of the curable composition.

[0060] The equivalent ratio in the curable composition is preferably 1.05 or more and 2.9 or less. The equivalent ratio in the curable composition is the equivalent ratio of the curing agent to the main agent constituting the binder, specifically, the ratio of the number of active hydrogens of the curing agent to the number of functional groups of the component constituting the main agent contained in the curable composition. Therefore, when the binder is composed of an epoxy group-containing compound and an amine, it is the equivalent of the active hydrogen of the amino group contained in the amine relative to the equivalent of the epoxy group contained in the epoxy group-containing compound, and when the binder is composed of an epoxy group-containing compound, a polyfunctional (meth)acrylate, and an amine, it is the equivalent of the active hydrogen of the amino group relative to the sum of the equivalent of the epoxy group contained in the epoxy group-containing compound and the equivalent of the (meth)acryloyl group contained in the polyfunctional acrylate compound. Furthermore, when the binder is composed of an epoxy group-containing compound and a thiol, it is the ratio of the equivalent of active hydrogen of the thiol group contained in the thiol to the equivalent of the epoxy group contained in the epoxy group-containing compound. Furthermore, when the binder is composed of an epoxy group-containing compound, an amine, and a thiol, it is the ratio of the sum of the equivalent of active hydrogen of the thiol group contained in the thiol and the equivalent of active hydrogen of the amino group contained in the amine to the equivalent of the epoxy group contained in the epoxy group-containing compound. By making the equivalent ratio of the functional group 1.05 or more, the number of active hydrogens in the amino group becomes appropriate, and a certain reaction proceeds even in the early stage of curing, making it easier to obtain fast curing properties. Also, by making it 2.9 or less, the number of active hydrogens in the amino group does not become too large, the compression load in the early stage of curing is reduced, and the usable time is easily extended. Also, by making the equivalent ratio within the above-mentioned specified range, it is easier to adjust the adhesive strength to an appropriate range. The equivalent ratio of the functional groups is more preferably 1.2 or more, further preferably 1.3 or more, even more preferably 1.4 or more, and is more preferably 2.6 or less, further preferably 2.1 or less, even more preferably 1.8 or less.

[0061] The epoxy group equivalent can be obtained by dividing the content (g) of the epoxy resin contained in the curable composition by the epoxy equivalent (g / eq). However, when two or more epoxy resins are contained, the epoxy group equivalent can be obtained by summing the values ​​obtained by dividing the content (g) of each epoxy resin by the epoxy equivalent (g / eq). The equivalent weight of active hydrogen of the amino group can be obtained by dividing the content (g) of the amine in the curable composition by the active hydrogen equivalent weight (g / eq) of the amine. However, when two or more amines are contained, the equivalent weight can be obtained by summing the values ​​obtained by dividing the content (g) of each amine by the active hydrogen equivalent weight (g / eq). Furthermore, the equivalent weight of the (meth)acryloyl group can be obtained by dividing the content (g) of the acrylate compound contained in the curable composition by the (meth)acryloyl equivalent weight (g / eq). However, when two or more acrylate compounds are contained, the equivalent weight can be obtained by summing values ​​obtained by dividing the content (g) of each acrylate compound by the (meth)acryloyl equivalent weight (g / eq). The epoxy equivalent (g / eq) can be obtained by dividing the molecular weight of the epoxy resin by the number of epoxy groups per molecule. The active hydrogen equivalent (g / eq) can be obtained by dividing the molecular weight of the amine by the number of active hydrogens per molecule. Furthermore, the (meth)acryloyl equivalent (g / eq) can be obtained by dividing the molecular weight of the acrylate compound by the number of (meth)acryloyl groups per molecule. The equivalent amount of active hydrogen in a thiol group is, for example, a value obtained by multiplying the amount of active hydrogen (mol / g) per unit amount of thiol in the adhesive by the amount of thiol contained in the adhesive. However, when two or more thiols are contained, the equivalent amount is the sum of the values ​​obtained by multiplying the amount of active hydrogen (mol / g) per unit amount of each thiol by the amount of each thiol contained in the adhesive. Furthermore, when both amine and thiol are contained, the equivalent of active hydrogen of the amino group and the thiol group is the sum of the equivalent of active hydrogen of the amino group and the equivalent of active hydrogen of the thiol group in the adhesive.

[0062] The molecular weight, the equivalent weight of epoxy groups, the equivalent weight of active hydrogen, and the number of (meth)acryloyl groups can be measured by a mass spectrometer (GC-MS or LC-MS). In addition, when only the molecular weight can be identified by a mass spectrometer, the number (equivalent weight) of epoxy groups and the number (equivalent weight) of active hydrogen per molecule can be determined by NMR ( 1 It can be identified by NMR spectroscopy (H NMR, etc.). However, when the sample is a mixture, it is preferable to isolate each component by GPC (gel permeation chromatography) or HPLC (high performance liquid chromatography) before measuring NMR. When the structural formula of the epoxy resin is known, the molecular weight and the number of epoxy groups are the molecular weight and the number of epoxy groups of the epoxy resin that can be calculated from the structural formula. When the structural formula of the amine is known, the molecular weight and the number of active hydrogens are the molecular weight and the number of active hydrogens of the amine that can be calculated from the structural formula. The same applies to acrylate compounds. The same applies to thiols. The number of active hydrogens in an amine is 1 for NHR2 (secondary amino group) and 2 for NH2R (primary amino group) (wherein, in NHR2 and NH2R, R is a functional group other than active hydrogen, i.e., the part of the amine other than the NH or NH2). The number of active hydrogens in a thiol is defined as SHR being 1 (where R is a functional group other than active hydrogens, that is, a portion of a thiol other than the SH).

[0063] The binder content in the adhesive is preferably 8% by volume or more and 55% by volume or less, based on the total volume of the adhesive. If it is equal to or more than the lower limit, the thermally conductive filler can be appropriately dispersed in the thermally conductive member and the adhesive. In addition, it is possible to prevent the viscosity of the adhesive from becoming higher than necessary. Furthermore, if it is equal to or less than the upper limit, it becomes easier to include a certain amount or more of the thermally conductive filler in the adhesive. The binder content in the adhesive is more preferably 15% by volume or more and 45% by volume or less, and even more preferably 18% by volume or more and 38% by volume or less.

[0064] [Thermal conductive filler] The adhesive of the present invention contains a thermally conductive filler. When the adhesive contains a thermally conductive filler, the thermal conductivity of the thermally conductive member formed from the adhesive is improved. Examples of the thermally conductive filler include metals, metal oxides, metal nitrides, metal hydroxides, carbon materials, oxides, nitrides, carbides, etc. The shape of the thermally conductive filler includes spherical and amorphous powders. In the thermally conductive filler, examples of metals include aluminum, copper, nickel, etc., examples of metal oxides include aluminum oxide, magnesium oxide, zinc oxide, etc., such as alumina, and examples of metal nitrides include aluminum nitride. Examples of metal hydroxides include aluminum hydroxide. Further, examples of carbon materials include spherical graphite. Examples of oxides, nitrides, and carbides other than metals include quartz, boron nitride, and silicon carbide. Among these, aluminum oxide is preferred from the viewpoint of improving the heat dissipation of the thermally conductive member, and aluminum hydroxide is preferred when it is desired to increase the flame retardancy. It is also preferable to use aluminum oxide and aluminum hydroxide in combination. The thermally conductive fillers may be used alone or in combination of two or more of the above.

[0065] The average particle size of the thermally conductive filler is preferably 0.1 μm or more and 200 μm or less, more preferably 0.5 μm or more and 150 μm or less, and even more preferably 1 μm or more and 110 μm or less. It is preferable to use a small-particle-size thermally conductive filler having an average particle size of 0.1 μm or more and 5 μm or less in combination with a large-particle-size thermally conductive filler having an average particle size of more than 5 μm and 200 μm or less in combination as the thermally conductive filler. By using thermally conductive fillers with different average particle sizes, the filling rate can be increased. The average particle size of the thermally conductive filler can be measured by observation using an electron microscope, etc. More specifically, for example, the particle sizes of 50 random thermally conductive fillers can be measured using an electron microscope or optical microscope, and the average value (arithmetic mean value) can be used as the average particle size.

[0066] The content of the thermally conductive filler in the curable composition is preferably 40% by volume or more and 90% by volume or less with respect to the total volume of the adhesive. If it is equal to or more than the above lower limit, a certain level of thermal conductivity can be imparted to the adhesive. In addition, by making the content of the thermally conductive filler equal to or less than the above upper limit, the thermally conductive filler can be appropriately dispersed in the thermally conductive member, and the viscosity of the adhesive can be prevented from becoming higher than necessary. In the present invention, the viscosity of the adhesive can be reduced to make it easier to increase the content of the thermally conductive filler. The content of the thermally conductive filler in the adhesive is more preferably 50% by volume or more and 85% by volume or less, and even more preferably 60% by volume or more and 78% by volume or less. The content of the thermally conductive filler in the curable composition, expressed in parts by mass, is preferably 150 parts by mass or more and 3,000 parts by mass or less, more preferably 200 parts by mass or more and 2,000 parts by mass or less, and even more preferably 300 parts by mass or more and 1,000 parts by mass or less, relative to 100 parts by mass of the binder.

[0067] (Dispersant) The curable composition of the present invention may contain a dispersant. Examples of the dispersant include polymeric dispersants. Examples of the polymeric dispersants include polymeric compounds having functional groups. Examples of the polymeric compounds include acrylic, vinyl, polyester, polyurethane, polyether, epoxy, polystyrene, amino, and silicone compounds. Examples of the functional groups include carboxyl groups, phosphoric acid groups, sulfonic acid groups, carboxylate groups, phosphoric acid ester groups, sulfonic acid ester groups, hydroxyl groups, amino groups, quaternary ammonium bases, and amide groups. In addition, the dispersant may be other than polymeric dispersants, and may be, for example, an alkoxysilane compound. The content of the dispersant in the adhesive is preferably from 0.1 to 10 parts by mass, more preferably from 0.2 to 5 parts by mass, and even more preferably from 0.4 to 3 parts by mass, relative to 100 parts by mass of the binder.

[0068] (water) The curable composition of the present invention may contain water. When the adhesive contains water, the water functions as a catalyst, making it easier to promote the reaction between the base agent and the curing agent, particularly between the acrylic compound and the amine. The water content is preferably 0.1% by mass or more and 3.0% by mass or less based on the total amount of the curable composition. When the water content is 0.3% by mass or more, the reaction between the base agent and the curing agent can be appropriately promoted by water. In addition, when the water content is 2.0% by mass or less, problems such as a decrease in the physical properties of the cured adhesive due to an excess amount of water or a shortened pot life due to excessive curing due to water are unlikely to occur. The water content is more preferably from 0.3% by mass to 2.0% by mass, and more preferably from 0.5% by mass to 1.5% by mass. Furthermore, when the adhesive contains water, the curing reaction is likely to proceed even with a relatively small amount of curing agent, and the gel point can be made relatively fast even with a relatively low equivalent ratio. The water content in the curable composition can be determined by measurement using the Karl Fischer method.

[0069] (Other additives) The curable composition of the present invention may contain additives other than those described above. Examples of such additives include curing catalysts such as bisphenol F that promote the reaction between the base agent other than water and the curing agent, reaction rate control agents (reaction retarders) that suppress the reaction between the base agent and the curing agent, thixotropy-imparting agents such as amides, flame retardants, plasticizers, antioxidants such as phenolic antioxidants, colorants, and the like. When a plasticizer is used, it is preferable to use one having a high molecular weight, and it is more preferable to use a reactive plasticizer or a substantially non-volatile plasticizer.

[0070] <Supply form> The adhesive of the present invention may be supplied in the form of a one-component type or a two-component type consisting of a combination of a first part and a second part, but from the viewpoint of storage stability, the two-component type is preferred. In a two-component adhesive, the volume ratio of the first agent to the second agent (second agent / first agent) is preferably 1 or close to 1, specifically, preferably 0.9 to 1.1, and more preferably 0.95 to 1.05. In this way, by setting the volume ratio of the first agent to the second agent to 1 or close to 1, the adhesive can be easily prepared.

[0071] In a two-component adhesive, both the first and second agents are liquid at room temperature (25°C), and it is preferable that the compression loads of the first and second agents are the same, or if the compression loads are different, the difference between the compression loads is small. In this way, by making the compression loads of the first and second agents the same or close to each other, it becomes easier to mix the adhesive uniformly. Specifically, the difference in compressive load between the first agent (N) and the second agent (N) is preferably 450 N or less, more preferably 250 N or less, and even more preferably 50 N or less. The method for measuring the compressive load is as shown in the examples.

[0072] More specifically, the two-part adhesive may have a first part containing a base agent of the binder, and a second part containing a hardener of the binder. The hardener may be one that hardens when mixed with the first part. The structure of the two-part adhesive will be described in detail below, taking as an example a case where the binder is an epoxy type.

[0073] In two-part adhesives, the first part contains a base agent but does not need to contain a hardener, while the second part contains a hardener but does not need to contain a base agent. However, the second part may contain a base agent as long as it does not react with the hardener.

[0074] The thermally conductive filler is contained in at least one of the first and second parts, but is preferably contained in both the first and second parts. Therefore, it is preferable that the first part contains a base agent and a thermally conductive filler, and the second part contains a curing agent and a thermally conductive filler. It is even more preferable that the first part does not contain a curing agent, and the second part does not contain a base agent. It is even more preferable that the base agent of the adhesive is entirely contained in the first part, and the curing agent of the adhesive is entirely contained in the second part.

[0075] As described above, the thermally conductive filler is preferably contained in both the first and second agents, and more preferably is contained approximately evenly in the first and second agents. Specifically, the ratio (volume ratio) of the content of the thermally conductive filler in the second agent to the content of the thermally conductive filler in the first agent is preferably 0.67 to 1.5, more preferably 0.83 to 1.2, and even more preferably 0.91 to 1.1. By distributing the thermally conductive filler approximately evenly in the first and second agents, it becomes easier to reduce the compression load difference between the first and second agents, and also easier to bring the volume ratio of the first and second agents closer to 1.

[0076] The difference in compressive load between the first and second agents can also be adjusted by the viscosity of the epoxy group-containing compound or the curing agent such as an amine used. For example, specifically, if you want to lower the viscosity of the first agent containing an epoxy group-containing compound, you can use a low-viscosity epoxy group-containing compound or increase the content. You can also adjust the viscosity to be low by adding a dispersant or plasticizer.

[0077] The closer the densities of the first and second agents are to each other, the easier they may be to mix, and the smaller the difference between their densities, the better. Specifically, the ratio of the density of the first agent to the density of the second agent (also called the density ratio) is preferably 0.7 to 1.4, more preferably 0.8 to 1.2, and even more preferably 0.9 to 1.1. In order to reduce the density ratio, the content of the thermally conductive filler in the first and second agents may be adjusted within the above range. In the two-liquid type, the dispersant and other additives may be contained in one or both of the first and second agents as necessary. For example, when the thermally conductive filler is contained in both the first and second agents, the dispersant may be contained in both the first and second agents. In addition, although water may be contained in either the first or second agent, it is preferable to contain water in the second agent and not in the first agent.

[0078] In a two-part adhesive, the ratio of the functional group concentration (mol / g) of the second part to the functional group concentration (mol / g) of the first part is preferably 1.05 to 2.9. By setting the functional group concentrations of the first and second parts within the above range, when the first and second parts are mixed in a volume ratio of 1:1, the base agent and the curing agent react at an appropriate equivalent ratio, resulting in fast curing properties and a long pot life. The functional group concentration ratio is more preferably 1.2 or more, further preferably 1.3 or more, even more preferably 1.4 or more, and more preferably 2.6 or less, further preferably 2.1 or less, even more preferably 1.8 or less.

[0079] The functional group concentration is the concentration of functional groups contained in the base or curing agent that can react with the curing agent or base, and in epoxy group-containing compounds, the epoxy group is the functional group, and the number of epoxy groups per unit amount (g) is the functional group concentration. In addition, in amines and thiols, the active hydrogen is the functional group, and the number of active hydrogen per unit amount (g) is the functional group concentration. For example, in a preferred embodiment, the first agent contains an epoxy group-containing compound and a polyfunctional acrylate compound but does not contain an amine or a thiol, and the second agent contains either an amine or a thiol but does not contain an epoxy group-containing compound or a polyfunctional acrylate compound. In this case, the total concentration of the epoxy group and (meth)acryloyl group in the first agent is the functional group concentration of the first agent, and the concentration of the active hydrogen of the amine and thiol in the second agent is the functional group concentration of the second agent.

[0080] When the adhesive is a two-part type, the first agent and the second agent are preferably filled in separate containers, specifically, the first agent is filled in the first container and the second agent is filled in the second container. The first container and the second container may be separate or integrated. By integrating the first container and the second container, it becomes easy to supply the adhesive as a container set to the demand destination. In this specification, the first container filled with the first agent and the second container filled with the second agent may be collectively referred to as a container set.

[0081] Examples of the container include, but are not limited to, a syringe, a cartridge, a pail can, a drum can, and the like. For example, when filling a syringe, it is preferable to use a two-liquid parallel type syringe. As shown in FIG. 1, a two-liquid parallel type syringe 30 is a combination of a first syringe 31 constituting a first container and a second syringe 32 constituting a second container, which are arranged in parallel. The first agent 35 and the second agent 36 filled in the syringes 31 and 32 may be discharged from the syringe as a dispenser and mixed.

[0082] In addition, when a cartridge is used, the container set is composed of a first cartridge constituting the first container and a second cartridge constituting the second container, and these cartridges may be integrated. Note that the cartridge is usually set in a syringe (e.g., a first syringe, a second syringe) or the like, and the first agent delivered from the first cartridge and the second agent delivered from the second cartridge are preferably delivered from the respective outlets of the first syringe and the second syringe as dispensers and mixed.

[0083] The first and second agents may be mixed in a mixer such as a static mixer. For example, as shown in Fig. 1, a static mixer 38 is connected to the outlet 31A of the first syringe 31 and the outlet 32A of the second syringe 32, and the first agent 35 and the second agent 36 discharged from the respective outlets 31A, 32A can be mixed inside the mixer 38. The mixture (curable composition) obtained by mixing in the mixer 38 may be discharged from the outlet 39 of the mixer 38. Each of the syringes 31, 32 may have a structure in which the openings of the barrels 33A, 34A, into which the first agent 35 and the second agent 36 are respectively filled, are closed by lids 33B, 34B. In the syringe 30 shown in Fig. 1, the first agent 35 and the second agent 36 may be ejected from each of the ejection ports 31A, 32A by being pushed out by pistons (not shown) inserted from the openings after the lids 33B, 34B are removed.

[0084] 2, the container set may include a first pail 41 constituting the first container and filled with a first agent 45, and a second pail 42 constituting the second container and filled with a second agent 46. Each pail 41, 42 includes, for example, container bodies 43A, 44A filled with the first agent 45 and the second agent 46 and having an opening, and lids 43B, 44B for closing the openings of each container body 43A, 44A.

[0085] (Method of preparing adhesive) When the adhesive of the present invention is a two-liquid type, the first agent and the second agent may be obtained by mixing the components constituting the first agent and the second agent, respectively. Similarly, when the adhesive is a one-liquid type, the components constituting the adhesive may be obtained by mixing them. The method of mixing the components is not particularly limited, but for example, it is preferable to add a thermally conductive filler, which is mixed as necessary, and additives such as a dispersant, which is mixed as necessary, to the binder, and then stir or knead to prepare the adhesive.

[0086] The thermally conductive filler may be surface-treated with a dispersant before being mixed with the binder. The thermally conductive filler is surface-modified in advance by being surface-treated with a dispersant in advance. The adhesive may then be prepared by mixing the thermally conductive filler that has been surface-modified in advance with the binder. The method of pre-treating the surface with a dispersant is not particularly limited, and may be a known method, for example, a wet treatment method, a dry treatment method, etc. may be used. In the wet treatment method, for example, a thermally conductive filler is added and mixed in a treatment liquid in which a dispersant is dispersed or dissolved in a solvent, and then the dispersant is bonded or attached to the surface of the thermally conductive filler by drying, heat treatment, washing, etc. In addition, the dry treatment method is a method of surface treatment without using a dispersion medium, and specifically, a dispersant is mixed with a thermally conductive filler, stirred with a mixer, etc., and then heat treated to bond or attach the dispersant to the surface of the thermally conductive filler.

[0087] [Thermal conductive material] The adhesive of the present invention may be used as a thermally conductive member. The adhesive of the present invention becomes a thermally conductive member when cured. The thermally conductive member of the present invention includes a polymer matrix and a thermally conductive filler. The polymer matrix is ​​formed by curing a binder, and the thermally conductive filler is dispersed in the polymer matrix and held by the polymer matrix. Therefore, for example, when the binder is an epoxy-based binder, the polymer matrix is ​​formed of a cured epoxy resin. The thermally conductive member may be disposed between two members, such as a heat generating member and a heat sink. The heat generating member may be an electronic component that generates heat, such as a battery. The heat sink may be a housing or a cooling member, such as a cooling plate.

[0088] The details of the thermally conductive filler in the thermally conductive filler are the same as those of the thermally conductive filler in the adhesive, and therefore the description thereof will be omitted. The details of the binder for forming the polymer matrix are also the same as those of the binder in the adhesive, and therefore the description thereof will be omitted. The same applies to the dispersant and other additives. However, while the binder content and the thermally conductive filler content are stated above in terms of the volume of the entire adhesive, the thermally conductive member is formed from adhesive, and therefore the above-mentioned content based on the volume of the entire adhesive can be regarded as the content based on the volume of the entire thermally conductive member in the thermally conductive member.

[0089] [Application] The adhesive and thermally conductive member of the present invention can be used in various applications, for example, in various electronic device applications such as battery assemblies such as lithium ion battery (LiB) assemblies, power electronic devices, electronic packaging, LEDs, solar cells, and electric grids. Among these, the adhesive and thermally conductive member are preferably used in battery assemblies, and more preferably used in LiB assemblies. Therefore, in a preferred embodiment of the present invention, a battery assembly including the thermally conductive member described above is provided. Note that the battery assembly such as the LiB assembly can be preferably used for automobiles.

[0090] In battery assembly applications, the adhesive and thermally conductive member of the present invention are preferably used as a gap material for a battery assembly. In one embodiment, the adhesive and thermally conductive member of the present invention are preferably used as a gap material for a battery module, and more preferably used as a gap material for a battery module. An example in which the thermally conductive member of the present invention is applied to a battery module will be described below.

[0091] The battery module includes a gap material made of a thermally conductive material, a plurality of battery cells, and a module housing that stores the plurality of battery cells, and the gap material is disposed inside the module housing. The gap material made of a thermally conductive material is filled between the battery cells and between the battery cells and the module housing, and the filled gap material is in close contact with the battery cells and the module housing. As a result, the gap material between the battery cells has a function of maintaining the battery cells in a spaced apart state. In addition, the gap material between the battery cells and the module housing is in close contact with both the battery cells and the module housing, and has a function of transferring heat generated in the battery cells to the module housing.

[0092] FIG. 3 shows a specific configuration of the battery module. FIG. 4 shows a specific configuration of each battery cell. As shown in FIG. 3, a plurality of battery cells 11 are arranged inside the battery module 10. Each battery cell 11 is laminated and enclosed in a flexible exterior film, and has an overall shape of a flat body that is thin compared to its height and width. As shown in FIG. 4, the positive electrode 11a and the negative electrode 11b of such a battery cell 11 are exposed to the outside, and the central part 11c of the flat surface is formed to be thicker than the crimped end part 11d.

[0093] As shown in Fig. 3, the battery cells 11 are arranged so that their flat surfaces face each other. In the configuration of Fig. 3, the gap material 13 is not filled so as to cover the entirety of the multiple battery cells 11 stored inside the module housing 12. The gap material 13 is filled so as to fill gaps that exist in a part (bottom part) inside the module housing 12. The gap material 13 is filled between the battery cells 11 and between the battery cells 11 and the module housing 12, and is in close contact with the surfaces of the battery cells 11 in these parts and the inner surface of the module housing 12.

[0094] The gap material 13 filled between the battery cells 11 is adhered to the surfaces of both battery cells 11, but the gap material 13 itself has appropriate elasticity and flexibility, and therefore can mitigate distortion caused by external force even if an external force that displaces the gap between the battery cells 11 is applied. Therefore, the gap material 13 has the function of maintaining the battery cells 11 in a spaced state. The gap material 13 filled in the gap between the battery cell 11 and the inner surface of the module housing 12 is also tightly bonded to the surface of the battery cell 11 and the inner surface of the module housing 12. As a result, heat generated inside the battery cell 11 is transferred via the gap material 13 bonded to the surface of the battery cell 11 to the inner surface of the module housing 12 which is in close contact with the other surface of the gap material 13.

[0095] The gap material 13 may be formed in the battery module 10 by applying a liquid adhesive with a general dispenser and then curing the liquid adhesive. As described above, the adhesive of the present invention has a low viscosity, and therefore the workability during the formation of the gap material 13 is improved. When forming the gap material 13, it is preferable to use a two-component adhesive as described above. The two-component adhesive is easy to store, and if mixed immediately before use, it is difficult to harden when applied with a dispenser, and can be quickly hardened after application. Application with a dispenser is also preferable in that the liquid adhesive can be filled relatively deep inside the housing 12 of the battery module 10.

[0096] The gap material 13 covering the battery cells 11 preferably covers 20 to 40% of each battery cell 11 on one side of the battery cells 11. By covering 20% ​​or more, the battery cells 11 can be stably held. In addition, by sufficiently covering the battery cells that generate a large amount of heat, heat dissipation efficiency is improved. On the other hand, by covering 40% or less, heat generated from the battery cells 11 can be efficiently dissipated, and weight increase and deterioration of workability can be prevented. In order to improve heat dissipation efficiency, it is preferable to cover the side of the battery cells 11 on which the electrodes 11a and 11b are located with the gap material 13, and it is more preferable to cover the entire electrodes 11a and 11b with the gap material 13. As described above, the battery module 10 can dissipate heat generated from the battery cells 11 to the module housing 12 via the gap material 13.

[0097] The gap material 13 is also preferably used in a battery pack having a plurality of battery modules 10 therein. The battery pack generally includes a plurality of battery modules 10 and a battery pack housing that houses the plurality of battery modules 10. In the battery pack, the gap material 13 can be provided between the battery modules 10 and the battery pack housing. This allows the heat dissipated to the module housing 12 as described above to be further dissipated to the battery pack housing, enabling effective heat dissipation.

[0098] In the above description, examples of the battery assembly are a battery module and a battery pack including a battery module. However, the battery assembly may be applied to a battery assembly that does not have a battery module, and it is also preferable to apply the battery assembly to a battery assembly having a cell-to-pack structure, for example.

[0099] FIG. 5 shows a schematic diagram of a battery assembly having a cell-to-pack structure. A battery assembly 20 having a cell-to-pack structure includes a plurality of battery cells 21 and a battery pack housing. The plurality of battery cells 21 are bonded to a base member 25 constituting the battery pack housing via a gap material 23 made of a thermally conductive member (cured product of adhesive). The base member 25 may be a cooling plate or the like. The gap material 23 in the battery assembly 20 may be formed in the same manner as the gap material 13 in the battery module, for example, by using a general dispenser. The adhesive of the present invention has a low viscosity, so that the workability when forming the gap material 23 is also good. In addition, the adhesive of the present invention has a fast curing property, but can reduce the compression load in the initial curing stage and can extend the usable time, so that the battery cell 21 can be bonded to the base member 25 with high workability even in a battery assembly having a cell-to-pack structure. EXAMPLES

[0100] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0101] [Thermal Conductivity] The thermal conductivity of the first and second adhesive agents was determined by measuring thermal resistance using a measuring device conforming to ASTM D5470-06. Specifically, a larger amount of adhesive was placed on the measurement die (the heat generating element side) to cover it, then sandwiched between heat sinks and compressed with a load of 30 psi until the adhesive thickness was 1.0 mm, 1.5 mm, and 2.0 mm, and the thermal resistance was measured for each thickness. The thickness can be adjusted with a spacer. For these three thermal resistance values, a graph was created with thickness on the horizontal axis and thermal resistance on the vertical axis, and an approximate straight line was found for the three points using the least squares method. The slope of the approximate straight line is the thermal conductivity. The thermal resistance was measured at 80° C. using an LW-9389 manufactured by Long Win Science and Technology Corporation. The area of ​​the measurement die was 1 inch×1 inch.

[0102] [Compressive load] 2 g of the adhesive prepared according to the formula was placed on an aluminum foil measuring 50 mm x 50 mm x 12 μm thick, wrapped in aluminum foil, and placed in a thermostatic chamber at 35°C for 6 minutes to obtain a measurement sample. After that, without placing the sample, a tool was pressed against the measurement point so that the load value was 3.6 kg, and a point 10 mm away from the jig was set as the measurement start position (zero point). The compression load of the measurement sample was measured under the conditions shown below. The first and second agents were also measured in the same manner. Test speed: 60mm / sec Jig size: 3cmφ Result reading: The displacement of 8.80 mm was taken as the compressive load value. Test environment: 25℃, 50% RH The obtained compression load value was used to evaluate the product on a four-point scale as follows: The compression load indicates the compression load at the initial stage of curing, and the lower the value, the easier it is to achieve temporary adhesion and the longer the usable time tends to be. (Evaluation Criteria) AA: 500N or less A: 800N or less B: More than 800N and less than 1000N C: More than 1000N and less than 1500N D: Over 1500N

[0103] [Adhesive strength (after 1 hour)] The adhesive strength of the cured adhesive at 18°C ​​(after 1 hour) was measured in accordance with DIN EN 1465 by the following method. First, two PET plates (trade name "PET-6010", manufactured by Takiron CI) with a width of 25 mm, length of 100 mm, and thickness of 2 mm were prepared. Then, the adhesive was applied to the longitudinal end of one plate so that the thickness after curing was 1 mm over a length of 5 mm over the entire width of the plate. Then, the longitudinal end of the other plate was overlapped on the applied adhesive, and the adhesive was cured by leaving it in this state under an environment of 18°C ​​and 50% RH for 1 hour to obtain a measurement sample. The measurement sample was formed by two PET plates overlapping over the entire width by a length of 5 mm, and the films were bonded together at the overlapping portion via a cured adhesive (size: 25 mm x 5 mm, thickness 1 mm), and had a size of 25 mm wide and 195 mm long.

[0104] [Adhesive strength (after 18 hours)] The adhesive strength (after 18 hours) was measured in the same manner as in the measurement of the adhesive strength (after 1 hour), except that the adhesive was left to stand for 18 hours after application.

[0105] [Gelation time] The elastic modulus G' and elastic modulus G'' were measured by a rheometer using a sample obtained by mixing the first and second agents. Specifically, a rheometer MCR-302e manufactured by Anton Paar was used to generate strain (distortion) using a Peltier plate at 25°C, and the changes in the elastic modulus G' and G'' of each sample were measured continuously for 120 minutes at a frequency of 1 Hz. The gelation time was determined as the time from the start of the measurement to the gel point at which the elastic modulus G' (storage modulus) and the elastic modulus G'' (loss modulus) became equal. The measurement was started immediately after mixing the first and second agents.

[0106] [Elastic modulus G' (after 15 minutes)] Using an Anton Paar rheometer MCR-302e, the above Peltier plate was used to generate strain at 25° C. while measuring at a frequency of 1 Hz, and the elastic modulus G′ was recorded 15 minutes after the start of the measurement. The measurement method and conditions were the same as those for the gelation time described above.

[0107] [Elastic modulus G'' (after 15 minutes)] Using an Anton Paar rheometer MCR-302e, measurements were performed at 25°C using a Peltier plate while generating strain at a frequency of 1 Hz, and the elastic modulus G'' was recorded 15 minutes after the start of the measurement. The measurement method and conditions were the same as those for the gelation time described above.

[0108] [Storage modulus (after 60 minutes)] Using an Anton Paar rheometer MCR-302e, a Peltier plate was used to generate strain at 25°C, and measurements were performed at a frequency of 1 Hz, and the elastic modulus G' was recorded 60 minutes after the start of the measurement. The measurement method and conditions were the same as those for the gelation time described above.

[0109] [Examples 1 to 6, Comparative Examples 1 to 3] The first and second parts were prepared by mixing the components according to the formulations in Tables 1 and 2. The prepared first and second parts were each filled into a 50cc two-liquid parallel cartridge, and mixed at room temperature in a volume ratio of 1:1 using a static mixer to obtain an adhesive. The physical properties of the obtained adhesive were determined, and evaluation tests were also carried out.

[0110] The components used in each of the Examples and Comparative Examples were as follows. (Epoxy group-containing compound) Bisphenol F epoxy resin: Product name "jER806", manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 165g / eq, molecular weight 330, viscosity (25℃) 2000mPa·s (catalog value) Multifunctional epoxy resin: Product name "EX-321", Nagase ChemteX Corporation, molecular weight 280, epoxy equivalent 140g / eq, viscosity (25℃) 130mPa·s (catalog value), trimethylolpropane polyglycidyl ether Monofunctional epoxy resin: Aliphatic glycidyl ether (aliphatic alcohol is C 12-14 ), product name "Epogosei ML", manufactured by Yokkaichi Synthetic Co., Ltd., epoxy equivalent 282g / eq, number of functional groups 1, molecular weight 282 Glycidyl ether: Trade name "Denacol EX146", Nagase ChemteX Corporation, molecular weight 225, 4-t-butylphenyl glycidyl ether, epoxy equivalent 225g / eq

[0111] (Polyfunctional acrylate compound) Dipentaerythritol hexaacrylate: Trade name "DPHA", manufactured by Daicel Ornix Corporation, molecular weight 520 (amine hardener) Trimethylolpropane poly(oxypropylene) triamine: Trade name "T-403", manufactured by HUNTSMAN, molecular weight 440, viscosity (25°C) 0.7 Pa·s (catalog value), active hydrogen equivalent 73.3 g / eq Poly(oxypropylene) diamine: Trade name "D-230", manufactured by HUNTSMAN, molecular weight 230, viscosity (25°C) 0.1 Pa·s (catalog value) Poly(oxypropylene) diamine: Trade name "D-400", manufactured by HUNTSMAN, molecular weight 430, active hydrogen equivalent 107.5 g / eq, viscosity (25°C) 0.3 Pa·s (catalog value) Polyamidoamine: Product name "ancamide506", manufactured by EVONIK, active hydrogen equivalent 110g / eq, viscosity (25℃) 0.3Pa·s, amidoamine Phenalkamine type Mannich base: Product name "NC-540", manufactured by Cardlight Japan Co., Ltd., active hydrogen equivalent 85g / eq, viscosity (25°C) 2Pa·s Amidoamine: Product name "TD-960", manufactured by DIC Corporation, active hydrogen equivalent 77g / eq, viscosity (25℃) 75Pa·s (catalog value) (thixotropic agent) Amide powder: Product name "6650", manufactured by Kusumoto Chemicals Co., Ltd. (Dispersant) Polymer dispersant (acidic group-containing copolymer) (Thermal conductive filler) Aluminum hydroxide 1: average particle size 1 μm Aluminum hydroxide 2: average particle size 10 μm Aluminum hydroxide 3: average particle size 50 μm Aluminum hydroxide 4: average particle size 105 μm (catalyst) Bisphenol F: Product name "Bisphenol F", manufactured by Honshu Chemical Co., Ltd. pure water

[0112] [Table 1]

[0113] [Table 2]

[0114] As is clear from the above examples, the curable thermally conductive adhesive that satisfies the requirements of the present invention has an appropriate gelation time, and one hour after mixing and applying each component, it is able to develop adhesive strength sufficient for temporary bonding. In addition, since the adhesive has a low compression load and low viscosity immediately after mixing, it can be attached to the adherend in a fully compressed state. And, since sufficient adhesive strength was developed 18 hours after mixing and applying each component, it was possible to create an adhesive that has fast curing properties and a long usable time. In contrast, in Comparative Example 1, the gelling time was too short, resulting in a high compressive load and high viscosity of the adhesive, which in turn shortened the pot life. In addition, the adhesive prepared in Comparative Example 2 had a gelation time that was too long and a storage modulus that was too low 60 minutes after the components were mixed and applied, so the adhesive did not harden sufficiently and did not exhibit sufficient adhesive strength even 18 hours after the components were mixed and applied. Furthermore, the adhesive prepared in Comparative Example 3 had a storage modulus that was too low 60 minutes after the components were mixed and applied, so the adhesive did not harden sufficiently, and therefore did not exhibit sufficient adhesive strength even 18 hours after the components were mixed and applied. [Explanation of symbols]

[0115] 10 Battery Module 11, 21 Battery cells 12 Battery module housing (module housing) 13, 23 Interstitial material 20 Battery Assembly 25 Base material 30 Syringe 31 First Syringe 31A First syringe outlet 32 Second Syringe 32A Second syringe outlet 33A, 34A Barrel 33B, 34B Barrel lid 35, 45 1st drug 36, 46 Second agent 38 Mixer 39 Mixer outlet 41 First Pail Can 42 Second Pail 43A, 44A Container body having openings 43B, 44B: Lid for closing the opening of the container body

Claims

1. A curable thermally conductive adhesive comprising a curable composition including a curable binder and a thermally conductive filler, It is a two-component curing type in which a first agent containing a base agent of the binder and a second agent containing a curing agent of the binder are mixed and used, the base agent contains an epoxy group-containing compound and a polyfunctional acrylate compound, the curing agent contains an amine, When the rheometer was used at a constant temperature of 25° C., the gel point at which the storage modulus and the loss modulus are equal was confirmed 5 to 60 minutes after the start of the rheometer measurement, and the storage modulus at 25° C. was 9.0×10 or less after 60 minutes had elapsed since the start of the rheometer measurement. 5 Pa or more, The curable thermally conductive adhesive, wherein the rheometer measurement is initiated by mixing the first part and the second part.

2. When measured with the rheometer, the loss modulus of the curable thermally conductive adhesive at 25° C. after 15 minutes from the start of the rheometer measurement was 3.0×10 5 The curable thermally conductive adhesive of claim 1 , having a viscosity of 0.05 Pa or less.

3. The curable thermally conductive adhesive according to claim 1 or 2, wherein the epoxy group-containing compound comprises a monofunctional epoxy group-containing compound.

4. 3. The curable thermally conductive adhesive of claim 1 or 2, wherein the binder comprises a Mannich base.

5. A curable thermally conductive adhesive as described in claim 1 or 2, wherein an equivalent ratio, which is the ratio of the equivalent of active hydrogen in the curing agent to the equivalent of functional groups of the components constituting the main agent, is 1.05 or more and 2.9 or less.

6. A supply form of the curable thermally conductive adhesive according to claim 1 or 2, A supply form of the curable thermally conductive adhesive in which the first part and the second part are filled in separate containers.

7. 7. The supply form of the curable thermally conductive adhesive according to claim 6, wherein the difference between the viscosity of the first part and the compressive load of the second part is 450 N or less.

8. 7. The supply form of the curable thermally conductive adhesive according to claim 6, wherein the ratio of the functional group concentration of the second part to the functional group concentration of the first part is 1.05 or more and 2.9 or less.

Citation Information

Patent Citations

  • Thermally conductive adhesive

    JP2012126762A

  • High thermal conductivity resin composition, high thermal conductivity cured product, adhesive film, sealing film, and semiconductor device using them

    JP2013006893A

  • Easily deformable aggregate, thermal conductive resin composition, thermal conductive member, and thermal conductive adhesive sheet

    JP2014162873A

  • Resin paste composition and semiconductor device

    JP2015135805A

  • Adhesive sheet, dicing tape-integrated adhesive sheet, film, manufacturing method of semiconductor device, and semiconductor device

    JP2016219619A